Machine Learning Implementation in Cognitive Radio Networks with Game-Theory Technique - Raj, Jennifer S. (IRO Journal on Sustainable Wireless Systems, 2020)
Significant enhancement of spectrum utilization can be performed by means of Cognitive Radio technology. A game theory based Cognitive Radio Network with Dynamic Spectrum Allocation model is proposed in this paper. M|M|1 queuing model is implemented along with Preemptive Resume Priority for accommodation of all the cases. An Incremental Weights-Decremental Ratios (IW-DR) algorithm based on priority-based scheduling is used for supplementing this theory. Regression models are used for restructuring and improving the efficiency of the system.
Keywords: Regression; Game Theory; Queuing Theory; Spectrum Allocation; Cognitive Networks